Dental age as indicator of adolescence - Filho, Omar Gabriel da Silva; Parteira, Naiara Jordão Souza; Lara, Tulio Silva; Bertoz, Francisco Antônio [UNESP] (FapUNIFESP (SciELO), 2012)
Aim: The purpose of the present study was to analyze the relationship between root formation of the first premolars and skeletal maturation stages identified in hand-wrist radiographs. Methods: A cross-sectional study was carried out involving the panoramic and hand-wrist radiographs obtained on the same date of 232 patients, 123 boys and 109 girls aged 4 years and 5 months to 17 years and 12 months. Root formation stages of the first premolars were related to the ossification stages of the sesamoid bone, epiphyseal stages of the phalanx of the thumb and epiphyseal stages of the radius. Results: The studied variables demonstrated statistically significant correlations. Conclusion: Roots of the lower first premolars do not reach 2/3 of their complete length before adolescence.
Keywords: Age determination by skeleton; Bone development; Orthodontics